Achieving sustainability requires systemic business transformation. (2020) - Waddock, Sandra
Non-technical summary: Achieving sustainability requires that businesses transform; however, it is virtually impossible in today's competitive environment for individual businesses to do what is needed to bring about systemic transformation. Instead, it is the context around businesses, including the public policy environment and changes by major actors, which must shift so that the pressures, constraints and demands on businesses can epimimetically drive their competitive instincts in the direction of wellbeing for all. Technical summary: Businesses and economic systems are implicated in the need to come into much better harmony with the realities of nature and in support of better human dignity and wellbeing to achieve sustainability in what is here called an epimimetic process. This article argues that while it is occasionally possible for leaders and companies to transform in the direction of sustainability or flourishing for all, it is unlikely that enough individual businesses can transform sufficiently while relying on an individual basis to achieve transformation. The context that constitutes the ecosystem in which businesses operate needs to change so that businesses themselves can change. Transforming businesses means significant change to the 'what' of businesses and their ecosystems – the purposes, perspectives, powers, practices and performance criteria shape businesses both internally and as external pressures. Businesses are unlikely to transform until the surrounding ecosystem demands that they do so. Social media summary: Individual businesses need public policy, activist and peer support to achieve systemic change towards sustainability.